2016
DOI: 10.1002/pat.3878
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel cardo-containing phenylethynyl-terminated polyimide with high thermal properties

Abstract: A phenylethynyl‐terminated reactive diluent [Card‐4‐phenylethynylphthalic anhydride (PEPA)], which contained fluorenyl cardo structures, was successfully synthesized and used as a modifier for flexible phenylethynyl‐terminated imide oligomer (PEI‐PEPA). The chemical structure, crosslink characterization, molecular weights, and thermal properties of the products were characterized. The imide systems with addition of 10, 20, 30, and 40 wt% Card‐PEPA to PEI‐PEPA (PEI‐PEPA‐Card) and their cured resin systems were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…At last, monomers with large pendant groups (like TFDB and 1,4,4‐6FAPB) are preferred, because they can also enhance the processability of the oligomers. Besides the CF 3 , monomers with the benzene ring or other pendant groups as side groups have also been investigated for PETIs. In recent years, Yokota and coworkers first used 2‐phenyl‐4,4′‐diaminodiphenyl ether ( p ‐ODA) to prepared dissoluble Tri A‐X .…”
Section: Introductionmentioning
confidence: 99%
“…At last, monomers with large pendant groups (like TFDB and 1,4,4‐6FAPB) are preferred, because they can also enhance the processability of the oligomers. Besides the CF 3 , monomers with the benzene ring or other pendant groups as side groups have also been investigated for PETIs. In recent years, Yokota and coworkers first used 2‐phenyl‐4,4′‐diaminodiphenyl ether ( p ‐ODA) to prepared dissoluble Tri A‐X .…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, PETIs have received sustained attention over these years. [6][7][8][9][10][11] In recent years, it was found that oligomers with calculated molecular weight of 750 g mol À1 showed good features for resin transfer molding (RTM) processing. RTM is more desirable for composite fabrication than conventional autoclave techniques because of its relatively low manufacturing cost and the solvent-free feature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, monomers with large pendant groups are preferred, because they can also enhance the processability of the oligomers. Besides TFDB and 1,4,4-6FAPB, monomers with the benzene ring [30][31][32][33] or other pendant groups 10,34 as side groups have also been investigated for PETIs. In recent years, Miyauchi et al firstly used 2-phenyl-4,4 0 -diaminodiphenyl ether (p-ODA) to prepare dissoluble Tri A-X.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al have also developed highly soluble PETIs from 4,4′‐(9‐fluorenylidene)dianiline (BAFL) and 4,4′‐oxydiphthalic anhydride (ODPA), and the oligoimide solution in N,N ‐dimethylacetamide (DMAc) with 30 wt% of solid content was used to prepared composites . Hu et al also prepared highly soluble oligoimides by the reaction of 2,3,3′,4′‐diphenyl ether tetracarboxylic acid dianhydride ( a ‐ODPA) and 3,4′‐oxydianiline (3,4′‐ODA), and the solid content of oligoimide solutions in NMP and DMAc can reach 40 wt% . However, the boiling points of these solvents are still too high to be removed during the fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…18 Hu et al also prepared highly soluble oligoimides by the reaction of 2,3,3′,4′-diphenyl ether tetracarboxylic acid dianhydride (a-ODPA) and 3,4′-oxydianiline (3,4′-ODA), and the solid content of oligoimide solutions in NMP and DMAc can reach 40 wt%. 19,20 However, the boiling points of these solvents are still too high to be removed during the fabrication. Hence, the oligoimides with high solubility in low-boiling point organic solvents in their fully imidized form are highly required.…”
mentioning
confidence: 99%